2017
DOI: 10.3390/ma10030249
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Anisotropy and Field‐induced Slow  Relaxation of Magnetization in Tetracoordinate CoII Compound [Co(CH3‐im)2Cl2]

Abstract: Static and dynamic magnetic properties of the tetracoordinate CoII complex [Co(CH3-im)2Cl2], (1, CH3-im = N-methyl-imidazole), studied using thorough analyses of magnetometry, and High-Frequency and -Field EPR (HFEPR) measurements, are reported. The study was supported by ab initio complete active space self-consistent field (CASSCF) calculations. It has been revealed that 1 possesses a large magnetic anisotropy with a large rhombicity (magnetometry: D = −13.5 cm−1, E/D = 0.33; HFEPR: D = −14.5(1) cm−1, E/D = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…The structural parameter δ proposed by Bocǎ et al was based on two angles, ∠(X-Co-X) (α) and ∠(Y−Co−Y) (β) for [CoX 2 Y 2 ] complexes, as δ = 2α Td − (α + β), where α Td = 109.5°, and it was suggested that this should directly correlate with D. 77 A later study by Nemec et al showed that such a relationship between δ and D is not linear in general. 78 In case of tetracoordinate [Co(NCS) 4 ] 2− of 1, the homoleptic nature of this complex made it difficult to calculate δ; however, the symmetry is close to ideal T d symmetry for which D = 0 and, indeed, the CASSCF/ NEVPT2 calculation resulted in a very small D value of −1.23 cm −1 (Table 2). Also, other homoleptic tetrahedral complexes of Co II were studied, 79 and an attempt to correlate D with the continuous symmetry measure (CShM) of SHAPE was reported.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural parameter δ proposed by Bocǎ et al was based on two angles, ∠(X-Co-X) (α) and ∠(Y−Co−Y) (β) for [CoX 2 Y 2 ] complexes, as δ = 2α Td − (α + β), where α Td = 109.5°, and it was suggested that this should directly correlate with D. 77 A later study by Nemec et al showed that such a relationship between δ and D is not linear in general. 78 In case of tetracoordinate [Co(NCS) 4 ] 2− of 1, the homoleptic nature of this complex made it difficult to calculate δ; however, the symmetry is close to ideal T d symmetry for which D = 0 and, indeed, the CASSCF/ NEVPT2 calculation resulted in a very small D value of −1.23 cm −1 (Table 2). Also, other homoleptic tetrahedral complexes of Co II were studied, 79 and an attempt to correlate D with the continuous symmetry measure (CShM) of SHAPE was reported.…”
Section: ■ Discussionmentioning
confidence: 99%
“…To discuss the relationship between the geometry of the coordination polyhedron and the magnetic anisotropy, we start with tetracoordinate Co II complexes. 78 In case of tetracoordinate [Co(NCS) 4 ] 2− of 1, the homoleptic nature of this complex made it difficult to calculate δ; however, the symmetry is close to ideal T d symmetry for which D = 0 and, indeed, the CASSCF/ NEVPT2 calculation resulted in a very small D value of −1.23 cm −1 (Table 2). Also, other homoleptic tetrahedral complexes of Co II were studied, 79 and an attempt to correlate D with the continuous symmetry measure (CShM) of SHAPE was reported.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Crystals 2020, 10, x FOR PEER REVIEW 2 of 14 choice of coordination number and polyhedral symmetry. It is well established that, for Co(II) compounds, very interesting results can be achieved for tetracoordinate coordination compounds exhibiting large distortion from ideal tetrahedral geometry [27]. To achieve significant distortions of coordination geometry, one can assume two viable strategies: (a) use of polydentate and sufficiently rigid ligands, (b) use of monodentate bulky ligands.…”
Section: Synthesis and Basic Characterizationsmentioning
confidence: 99%
“…13 It reads δ = 2α Td − (α), where α Td is the angle of the ideal tetrahedron (109.5°), α is the angle between the two Co-N/P bonds. Despite some limitations, 14 this relationship has proved to be successful in the prediction of sign and magnitude of D, such that more negative/positive δ should lead to more negative/positive value of D. Therefore, our attention has focused on compounds with rather large and negative parameter δ and these were further investigated for their static and dynamic magnetic properties. 14,15 Therefore, we opted to investigate the compound [CoCl 2 (dppf )] as a suitable SIM candidate, where dppf represents the 1,1′-ferrocenediyl-bis (diphenylphosphine).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some limitations, 14 this relationship has proved to be successful in the prediction of sign and magnitude of D, such that more negative/positive δ should lead to more negative/positive value of D. Therefore, our attention has focused on compounds with rather large and negative parameter δ and these were further investigated for their static and dynamic magnetic properties. 14,15 Therefore, we opted to investigate the compound [CoCl 2 (dppf )] as a suitable SIM candidate, where dppf represents the 1,1′-ferrocenediyl-bis (diphenylphosphine). This complex can be prepared by the reaction between dppf and CoCl 2 where both dppf and the resulting product [CoCl 2 (dppf )] are very well known, thoroughly studied (besides magnetic properties) 16 and even commercially available coordination compounds.…”
Section: Introductionmentioning
confidence: 99%